STRATEGIES IN TEACHING READING TO VISUALLY IMPAIRED STUDENTS - Setiawan, Wayan Agris Jodi; Adnyani, Luh Diah Surya; Suprianti, Gusti Ayu Putu (Universitas Pendidikan Ganesha, 2020)
This study aimed to determine the strategies that are used in teaching reading to visually impaired students and the challenges in teaching reading to visually impaired students in SLB Negeri 1 Tabanan. The research design used was a descriptive qualitative design. Subject of the study was the students with visually impaired in SLB Negeri 1 Tabanan which amounted 5 students. Data were collected by video recording, field note, and interview. Then, data were analyzed qualitatively. The results showed that (1) the English teacher used six strategies in teaching reading to visually impaired students in SLB Negeri 1 Tabanan, namely reading paper strategies (paper braille with pen reglet), reading e-text strategies (regular e-text with JAWS application), tracking support with JAWS application, auditory support (in the form of words and sentences level by using JAWS application), auditory strategies (live reader with a story entitled My School and live reader with multiple choice quizzes), and digital audio (files with a story entitled My School). (2) There were some challenges in teaching visually impaired students in SLB Negeri 1 Tabanan. One of them was the students were lack of vocabularies, so they could not response the lesson as good as normal students and the teacher needed longer time to teach those students. Second, the visually impaired students could not learn or did something individually, so they always needed assistance from the other people because visually impaired students could not see object around clearly. The last, the teacher looked a little difficult when showing an object to the students, because of the visual limitation experienced by students. It is suggested more strategies, software and application could be used to teach visually impaired students, and there will be more training or workshop for teachers so they have more experiences in dealing with students with special needs. Keywords: Strategies in Teaching Reading, Visually Impaired students